1963
DOI: 10.1021/ed040p234
|View full text |Cite
|
Sign up to set email alerts
|

The early history of carbon-14

Abstract: Traces the discovery and early history of carbon-14.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…These studies were the first in biology to make use of carbon‐14 and demonstrated that C . thermoaceticum incorporated 14 CO 2 equally into both carbons of acetate 32,33 . That C .…”
Section: The Discoverers Of Acetogens and Acetogenesismentioning
confidence: 92%
See 1 more Smart Citation
“…These studies were the first in biology to make use of carbon‐14 and demonstrated that C . thermoaceticum incorporated 14 CO 2 equally into both carbons of acetate 32,33 . That C .…”
Section: The Discoverers Of Acetogens and Acetogenesismentioning
confidence: 92%
“…The fixation of CO 2 proposed by Fontaine was demonstrated experimentally a few years later in 1945 with the landmark 14 C‐studies of Barker and Kamen 32,33 . These studies were the first in biology to make use of carbon‐14 and demonstrated that C .…”
Section: The Discoverers Of Acetogens and Acetogenesismentioning
confidence: 96%
“…Artificial radioisotopes could be generated by exposing targets to cyclotron radiation (Lawrence, ). In this way the radioisotopes 3 H (Alvarez & Cornog, ), 14 C (Ruben & Kamen, , for a history of 14 C discovery and production see Kamen, ) and 32 P (Hahn & Hevesy, ; Marshak, ) were discovered, and their use in metabolic studies immediately started.…”
Section: –1950 Stable Isotopes and Radioisotopes Of Light Bioelemmentioning
confidence: 99%
“…There the ammonium nitrate was exposed to slow-neutrons for weeks, eventually yielding significant amounts of the long lived radio-isotope of carbon (14C) (Ruben and Kamen 1941, Kamen 1963. He was clearly disappointed that I did not play an instrument.…”
Section: University Of California At Berkeley: Sam Ruben and Martin Kmentioning
confidence: 99%